2013
DOI: 10.1002/hyp.10099
|View full text |Cite
|
Sign up to set email alerts
|

Variability of unsaturated Bromide fluxes as measured through a layered volcanic vadose zone in New Zealand

Abstract: Abstract:The measured drainage fluxes through a layered volcanic vadose zone exhibited high spatial variability as a consequence of heterogeneous flow conditions. The drainage flux variability was quantified using automated equilibrium tension lysimeters, installed in close-proximity and resulted in high variability in the Br masses recovered from a conservative tracer experiment. The primary cause of the heterogeneous flow was attributed to textural changes occurring at the interface between volcanic layers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The importance of the spatial correlation structure was demonstrated by Schlüter et al (2012a), who concluded from numerical experiments that “increased isotropic, short‐range connectivity reduces non‐equilibrium, whereas anisotropic structures that are elongated in the direction of flow enforce it.” This blueprint for preferential flow is certainly matched by large structural pores (termed macropores ) that are almost ubiquitous in soil (Jarvis, 2007). Apart from macropore flow, funnel flow or focused recharge at the Darcy scale can also be induced by much larger scale structures of elongated geometry, such as tongue‐like soil horizon interfaces (e.g., Kulasekera and Parkin, 2011; Hardie et al, 2011) or inclined layers or lenses of contrasting permeability in the soil or vadose zone (e.g., Kung, 1990; Heilig et al, 2003; Barkle et al, 2014; Sohrt et al, 2014).…”
mentioning
confidence: 99%
“…The importance of the spatial correlation structure was demonstrated by Schlüter et al (2012a), who concluded from numerical experiments that “increased isotropic, short‐range connectivity reduces non‐equilibrium, whereas anisotropic structures that are elongated in the direction of flow enforce it.” This blueprint for preferential flow is certainly matched by large structural pores (termed macropores ) that are almost ubiquitous in soil (Jarvis, 2007). Apart from macropore flow, funnel flow or focused recharge at the Darcy scale can also be induced by much larger scale structures of elongated geometry, such as tongue‐like soil horizon interfaces (e.g., Kulasekera and Parkin, 2011; Hardie et al, 2011) or inclined layers or lenses of contrasting permeability in the soil or vadose zone (e.g., Kung, 1990; Heilig et al, 2003; Barkle et al, 2014; Sohrt et al, 2014).…”
mentioning
confidence: 99%
“…Their drainage flux and therefore their lower boundary has to proceed as in the natural soil, whereas the effect of the lower boundary got discussed controversially in literature. On the one hand, suction controlled devices got emphasized to work better than free draining lysimeters ( Vereecken and Dust , 1998; Zhu et al, 2002; Gee et al, 2009; Peters and Durner , 2009; Barkle et al, 2014) and on the other hand studies by Meissner et al (2010) yielded that there are no significant differences between both types for longer observation periods. Each of these effects or a combination of these problems could lead to deviations between the water regime of the lysimeter and the investigated field ( Hagenau et al, 2015).…”
Section: Introductionmentioning
confidence: 99%